2-Aminothiophene Derivatives—New Drug Candidates Against Leishmaniasis: Drug Design, Synthesis, Pharmacomodulation, and Antileishmanial Activity - Rodrigo Santos Aquino de Araújo; Vitória Gaspar Bernardo; Robert da Silva Tibúrcio; Danilo Cesar Galindo Bedor; Michel Leandro de Campos; Roberto Pontarolo; Julyanne Maria Saraiva de Sousa; Klinger Antonio da Franca Rodrigues; Marcus Tullius Scotti; Anuraj Nayarisseri; Pascal Marchand; Francisco Jaime Bezerra Mendonça-Junior (Pharmaceuticals)
Background/Objectives: Leishmaniasis is one of the 20 Neglected Tropical Diseases according to the WHO, affecting approximately 12 million people in four continents, generating serious public health problems. The lack of therapeutic options, associated with toxicity and the emergence of resistance to the few available drugs, makes it urgent to develop new drug options. In this context, the aims of this work are to expand the knowledge about the pharmacophore group responsible for the antileishmanial potential of 2-aminothiophene derivatives. Thus, new compounds were synthesized containing chemical modifications at the C-3, C-4, and C-5 positions of the 2-aminothiophene ring, in addition to the S-Se bioisosterism. Methods: Dozens of 2-AT and 2-aminoselenophen (2-AS) derivatives were sequentially synthesized through applications of the Gewald reaction and were then evaluated in vitro for their activities against L. amazonensis and for cytotoxicity against macrophages. Results: Several series of compounds were synthesized, and it was possible to identify some substitution patterns favorable to the activity generating compounds with IC50 values below 10 µM, such as the non-essentiality of the presence of a carbonitrile group at C-3; the importance of the presence and size of cycloalkyl/piperidinyl chains at C-4 and C-5 in modulating the activity; and the increase in activity without affecting the safety of the S/Se bioisosteric substitution. Conclusions: Taken together, these findings reaffirm the great potential of 2-aminothiophenes to generate antileishmanial drug candidates and offers contributions to the drug design of compounds with an even more promising profile for the problem of leishmaniasis.